Clinical Impact of BioFire Film Array in Pediatric Sepsis - Moraru, Gabriela M.; Chatani, Brandon; Martinez, Octavio; Scott, Gwendolyn; Tamariz, Leonardo; Mitchell, Charles D. (Journal of Pediatric Infectious Diseases, 2020)
Objective Rapid molecular tests are important components of antimicrobial stewardship programs (ASP) and for early and accurate diagnosis of sepsis etiology. Their utility in helping providers to de-escalate therapy remains a subject of debate, especially among patients with chronic conditions and indwelling devices.Methods We have conducted a retrospective cohort study of medical records from August 1, 2016 to July 31, 2018, following the implementation at our institution of the BioFire FilmArray blood culture identification panel (BioFire Diagnostics, Salt Lake City, Utah, United States). We have assessed the clinical impact of the assay looking at antimicrobial optimization and time needed to make this change in different pediatric wards.Results Two hundred and twenty-nine patients were included in our analysis. We identified a significant statistical difference between different pediatric wards regarding antimicrobial therapy optimization (p < 0.001) and between the type of therapeutic attitude related to BioFire result, escalation versus de-escalation, or no change (p < 0.03). The likelihood for an infectious disease consult requested upon BioFire result to lead to an antimicrobial regimen optimization was also statistically significant (p < 0.01). The positive BioFire results were associated with antimicrobial escalation in 81.4% of cases, with approximately 75% of changes made within 12 hours of the assay result.Conclusion Our study suggests that BioFire Film Array does not help de-escalating the therapy in patients with chronic disorders. Physician education and level of confidence in the assay remains an essential obstacle in maximizing the test performance in clinical practice. In recent years, the market for more sensitive and comprehensive rapid molecular diagnostic tests has evolved rapidly, requiring effective ASP to optimize the management of infectious diseases.
Keywords: rapid molecular test; bloodstream infections; clinical impact; pediatrics